History of pianoforte music and composers - Nicolet, Bessie Minerva (My University, 1907)
Introduction: Musical history is divided into two periods, ancient and modern, the Christian era being the division line. Each of these periods may be subdivided into two others, namely, the apprentice and master periods. During the apprentice period of ancient music, types of instruments were being found out, melodic or harmonic forms mastered or the total sense undergoing development. The period extends back to the earliest traces of music-beginning perhaps with the early Aryans in central Asia, whom Max Miller represents as circling around a family altar at sunrise and sunset with elapsed bands repeating in musical tones a hymn. From this early association of music with religious ritual and worship and out of which has come much of the tender regard we have for it as an expression of home and love in the higher aspects. In the master period the art of music suddenly burst forth, complete and satisfactory according to the principles recognized by the musicians of that time. The composers of music in ancient Greece had for instruments only lyres of six to eight strings. After ten centuries every suggestion in the compass of these had been carried out. All the leading types of instruments were discovered in the early part of human history. Egypt, Greece, India, and every great nation had forms of its own…
Citation: Nicolet, Bessie Minerva. History of pianoforte music and composers. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: History of Music; Types of Music; Influences on Music; Composers; Theses; Manuscripts (documents)